STRATEGI EFEKTIF BIMBINGAN KONSELING UNTUK MEMBANTU SISWA SD MENGATASI MASALAH BELAJAR - Marwantoro, Teguh (Universitas Muria Kudus, 2025)
Learning problems experienced by elementary school students require appropriate intervention through effective guidance and counseling (BK) strategies. This study aims to identify the most effective BK strategies in helping elementary school students overcome learning difficulties. The method used is a literature study with a Systematic Literature Review (SLR) approach, which analyzes academic sources such as SINTA-accredited journals, scientific books, and peer-reviewed articles published in the last ten years (2015–2025). The subjects in this study were scientific documents relevant to BK strategies at the elementary school level. The data collection instrument was a literature review guide based on inclusion and exclusion criteria. Data analysis was carried out using content analysis techniques with the stages of identification, categorization, synthesis of findings, and interpretation. The results of the study showed five main effective strategies: individual counseling, group counseling, collaboration with teachers and parents, development of learning skills, and a holistic approach. These strategies have been shown to improve students' academic understanding, social skills, learning efficiency, and reduce academic anxiety. These findings emphasize the importance of implementing comprehensive and evidence-based BK strategies to support the learning success of elementary school students.